Housekeeping by design : hotels and labor - Brody, David (Chicago : The University of Chicago Press, 2016)
One of the great pleasures of staying in a hotel is spending time in a spotless, neat, and organized space that you don t have to clean. That doesn t, however, mean the work disappears when we re not looking, someone else is doing it. With Housekeeping by Design, David Brody introduces us to those people the housekeepers whose labor keeps the rooms clean and the guests happy. Through unprecedented access to staff at several hotels, Brody shows us just how much work goes on behind the scenes and how much management goes out of its way to make sure that labor stays hidden. We see the incredible amount of hard physical work that is involved in cleaning and preparing a room, how spaces, furniture, and other objects are designed to facilitate a smooth flow of hidden labor, and, crucially, how that design could be improved for workers and management alike if front-line staff were involved in the design process. After reading this fascinating exposé of the ways hotels work or don t for housekeepers one thing is certain: checking in will never be the same again.
Chapter 1. Theoretically checking in -- Chapter 2. Design and the Chambermaid -- Chapter 3. A textbook case: Pedagogy and housekeeping -- Chapter 4. Laboriously unreal: Design and hotel impossible -- Chapter 5. Go green: design, hotels, and the sustainability paradox -- Chapter 6. We truly listened to our guests: rethinking the redesign of the hyatt regency chicago
Includes index.
Keywords: SUSTAINABLE BUILDINGS -- DESIGN AND CONSTRUCTION